Sex‐specific associations of obesity and N‐terminal pro‐B‐type natriuretic peptide levels in the general population - Suthahar, Navin; Meijers, Wouter C.; Ho, Jennifer E.; Gansevoort, Ron T.; Voors, Adriaan A.; van der Meer, Peter; Bakker, Stephan J.L.; Heymans, Stephane; van Empel, Vanessa; Schroen, Blanche; van der Harst, Pim; van Veldhuisen, Dirk J.; et al. (European journal of heart failure, 2018)
Background Obese subjects have lower natriuretic peptide levels, but males and females have different anthropometric characteristics and fat distribution. Whether obesity‐associated lowering of natriuretic peptides differs among males and females is unknown. Therefore, we investigated sex‐specific associations of obesity and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) levels among adults in the general population. Methods and results Using 8260 participants (50.1% females) from the Prevention of REnal and Vascular ENd‐stage Disease (PREVEND) cohort, we evaluated the relationship of NT‐proBNP levels with obesity‐associated parameters, i.e. waist circumference (WC), body mass index (BMI) and body weight in the overall population, and in males and females separately. NT‐proBNP levels were higher in females (median, interquartile range: 50.5, 28.2–87.0 ng/L) than in males (24.3, 10.1–54.6 ng/L; P < 0.001). In the overall population, NT‐proBNP levels were significantly lower in heavier individuals and displayed a ‘U‐shaped’ relationship with increasing WC, but were not associated with BMI. After sex stratification, there was no significant association between NT‐proBNP concentrations and anthropometric measures in females. However, in males increasing WC and BMI were associated with higher NT‐proBNP levels (P < 0.05) while increasing body weight was associated with slightly lower NT‐proBNP levels (P < 0.05). Age strongly confounded the association of NT‐proBNP levels with obesity, and age‐associated increases in NT‐proBNP were significantly higher in males than in females (P < 0.001). In multivariable adjusted analyses, the inverse association of obesity and NT‐proBNP levels was also significantly modified by sex: NT‐proBNP levels were lower with increasing WC, BMI and body weight among females compared with males (Pinteraction < 0.05). After also accounting for BMI, abdominal obesity was associated with lower NT‐proBNP levels in females, but not in males (Pinteraction < 0.001). Conclusions Natriuretic peptide deficiency in obesity mostly pertains to females with abdominal obesity, whereas the relationship between obesity and natriuretic peptides appears to be more complex in males.